Gestures of love : romancing performance in classical Hollywood cinema - Rybin, Steven, 1979- (SUNY series, horizons of cinema., 2017)
Gestures of Love" considers the viewer's enchantment with charismatic actors in film as the starting point for closely analyzing the performance of love in movies. Written with a thoughtful adoration for the actors who move us, Steven Rybin examines several of cinema's most beloved on-screen movie couples, including Katharine Hepburn and Cary Grant, Myrna Loy and William Powell, Carole Lombard and John Barrymore, Gene Tierney and Dana Andrews, Lauren Bacall and Humphrey Bogart, and Rock Hudson and Dorothy Malone. Using the classical genres of screwball comedy, film noir, and the family melodrama as touchstones, Rybin places the depiction of romance in films into dialogue with the viewer's own emotional bond to the actors on the screen. In doing so, he offers rich new analyses of such classic films as Bringing Up Baby, The Thin Man, Twentieth Century, Laura, To Have and Have Not, Tea and Sympathy, Written on the Wind, and more.